2021
DOI: 10.47093/2218-7332.2021.12.3.56-67
|View full text |Cite
|
Sign up to set email alerts
|

Neurological disorders in patients with long COVID syndrome and cell therapy methods for their correction a literature review

Abstract: The review presents the current understanding of the incidence and nature of neurological disorders in patients with the so-called long COVID syndrome. Symptoms, putative pathophysiological mechanisms, risk factors, search for methods of treatment and rehabilitation of patients using the patient's own hematopoietic cells are discussed. A search was carried out for scientific articles, including those published in peer-reviewed journals indexed in PubMed, Web of Science, Scopus and RSCI. The inclusion of stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Anxiety, depression, panic attacks, and sleep disturbances are frequently encountered as prevailing affective disorders among patients and individuals in the recovery phase of COVID-19 [91]. Alongside the aforementioned conditions, Mazza et al [92] have documented cases of post-traumatic stress disorder and symptoms of obsessive-compulsive disorder during the pandemic.…”
Section: Mental Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety, depression, panic attacks, and sleep disturbances are frequently encountered as prevailing affective disorders among patients and individuals in the recovery phase of COVID-19 [91]. Alongside the aforementioned conditions, Mazza et al [92] have documented cases of post-traumatic stress disorder and symptoms of obsessive-compulsive disorder during the pandemic.…”
Section: Mental Disordersmentioning
confidence: 99%
“…Gastrointestinal symptoms involve anorexia, abdominal pain, dyspepsia, and diarrhea. COVID-19 survivors may also experience long-lasting or newly developed skin conditions such as itching, hives, hair loss, and fibromyalgia [84,91]. A meta-analysis by Alkodaymi et al [100] revealed substantial heterogeneity among studies regarding the prevalence of all documented symptoms.…”
Section: Post-covid Syndromementioning
confidence: 99%